TECHNOLOGICAL PARADIGMS: A JUMP TO THE SIXTH OR A SLIP DOWN TO THE FOURTH - L. V. Ivanovskaya (Вестник университета)
The aim of this article is to analyse approaches to emphasizing the essence of the sixth technological paradigm (wave of innovation). The author uses the historical research method. By examining ideas on the technological paradigms (wave, cycle, paradigm, formation, etc.), the author shows the limitation of the purely economic approach to solving technological paradigms issues. The attention is paid also on the periodization of paradigms and there is an absence of a single logical basis in it. paradigms change. This circumstance does not allow us to speak about a really theoretical description of the process of changing paradigms. The situation is being considered from a wider historical perspective of the humankind existence (as a species), as a subject not only on a planetary scale. From this point of view, the essence of the sixth paradigm and the prospects for the evolution of paradigms are more clearly identified.